An Ontology for Unconventional Conflict - Hartley III, Dean S. (Understanding Complex Systems,, 2018)
This book describes the ontology structure, types of actors, their potential actions, and ways that actions can affect the things that are part of the conflict. An ontology of unconventional conflict supports the understanding of unconventional conflict in general. It also provides a tool for understanding and investigating a particular unconventional conflict. The ontology specifies the relations among the elements and supports creating a description of a particular situation. Unconventional conflict spans the range from natural disasters through human disagreements to irregular warfare (up to conventional war). Unconventional conflict involves damage to things and injuries to people; however, the critical factors are the actions, reactions, and opinions of people, including political, military, economic, social, infrastructure, and information components. This ontology supports and will appeal to military strategists, political scientists, economists, and politicians in understanding their planning for, and managing of these conflicts.